Investigation of the Feasibility of an Intervention to Manage Fall Risk in Wheeled Mobility Device Users with Multiple Sclerosis - Rice, Laura A. (Int J MS Care, 2018)
BACKGROUND: Falls are a common concern for wheeled mobility device users with multiple sclerosis (MS); however, no evidence-based fall prevention programs have been developed to meet the specific needs of the population. We examine the preliminary feasibility of a fall management intervention in wheeled mobility device users with MS. METHODS: Study participants were exposed to an intervention program targeting risk factors for falls, including transfer skills and seated postural control. The feasibility of the program was evaluated by assessing participant perspectives, cost, recruitment rates, study adherence, participant retention, safety, and the ability to collect primary and secondary outcomes, including fall frequency, concerns about falling, transfer quality, and seated postural control. RESULTS: 16 wheeled mobility device users completed the program, which was found to be feasible and was positively evaluated by participants. No adverse events were experienced. After exposure to the intervention, fall frequency significantly decreased (P < .001) and transfer quality (P = .001) and seated postural control (P = .002) significantly improved. No significant differences were found regarding concerns about falling (P = .728). CONCLUSIONS: This study examined the feasibility of an intervention program to manage fall risk in wheeled mobility device users with MS. The program was found to be feasible, and preliminary results showed the intervention to be effective in decreasing fall frequency. Additional testing is needed to further examine the efficacy and long-term impact of the intervention.